Oral field cancerization: Genetic profiling for a prevention strategy for oral potentially malignant disorders - Puspasari, Karlina; Pasaribu, Togu Andrie Simon; Surboyo, Meircurius Dwi Condro; Ayuningtyas, Nurina Febriyanti; Santosh, Arvind Babu Rajendra; Ernawati, Diah Savitri (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Oral cancer therapy, such as radiation or surgical treatment, has pernicious long-term effects that patients suffer throughout their life, the disability being considerable with delayed diagnosis. It is well known that many oral cancers develop from oral potentially malignant disorders (OPMDs). Patients diagnosed with OPMDs may have an increased risk of developing cancer anywhere in the oral cavity. Early detection and intervention could be essential prevention strategies to inhibit oral cancer progression. OPMDs may not immediately develop into carcinoma. However, this condition provides a "field” of specific abnormalities wherein evolving altered genetic cells can be explained with the "field cancerization” concept. Purpose: This review aims to describe the "field cancerization” concept in oral cancer and OPMD, which is expected to contribute to a better clinical management strategy for oral cancer prevention. Review: "Oral field cancerization” describes oral cancers that develop in multifocal areas of pre-cancerous changes. It can be found as histologically abnormal tissue surrounding the tumor, suggesting that oral cancer often consists of multiple independent lesions. Conclusion: The oral field cancerization concept should prompt healthcare professionals to remind their patients that frequent oral examination with histological studies and molecular testing is mandatory for those at high risk of developing malignancies.